COMBINED P16 AND HUMAN PAPILLOMAVIRUS TESTING PREDICTS HEAD AND NECK CANCER SURVIVAL - Salazar, C. R. (2014)
While its prognostic significance remains unclear, p16(INK4a) protein expression is increasingly being used as a surrogate marker for oncogenic human papillomavirus (HPV) infection in head and neck squamous cell carcinomas (HNSCC). To evaluate the prognostic utility of p16 expression in HNSCC, we prospectively collected 163 primary tumor specimens from histologically confirmed HNSCC patients who were followed for up to 9.4 years. Formalin fixed tumor specimens were tested for p16 protein expression by immunohistochemistry. HPV type-16 DNA and RNA was detected by MY09/11-PCR and E6/E7 RT-PCR on matched frozen tissue, respectively. P16 protein expression was detected more often in oropharyngeal tumors (53%) as compared with laryngeal (24%), hypopharyngeal (8%), or oral cavity tumors (4%; P<0.0001). With respect to prognosis, p16-positive oropharyngeal tumors exhibited significantly better overall survival than p16-negative tumors (log-rank test p=0.04), whereas no survival benefit was observed for non-oropharyngeal tumors. However, when both p16 and HPV DNA test results were considered, concordantly positive non-oropharyngeal tumors had significantly better disease-specific survival than concordantly negative non-oropharyngeal tumors after controlling for sex, nodal stage, tumor size, tumor subsite, primary tumor site number, smoking, and drinking (adjusted hazard ratio [HR]=0.04, 0.01–0.54). Compared with concordantly negative non-oropharyngeal HNSCC, p16(+)/HPV16(-) non-oropharyngeal HNSCC (n=13, 7%) demonstrated no significant improvement in disease-specific survival when HPV16 was detected by RNA (adjusted HR=0.83, 0.22–3.17). Our findings show that p16 immunohistochemistry alone has potential as a prognostic test for oropharyngeal cancer survival, but combined p16/HPV testing is necessary to identify HPV-associated non-oropharyngeal HNSCC with better prognosis.